2000
DOI: 10.1046/j.1432-1327.2000.00987.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and primary structure of a macromolecular‐translocation inhibitor II of glucocorticoid‐receptor binding to nuclei from rat liver

Abstract: The nuclear binding of the activated glucocorticoid-receptor (GR) is inhibited by endogenous macromolecules in vitro. Previously, we have separated the inhibitors into three species (MTI-I, MTI-II and MTI-III). In this study, we purified the most potent of the three species (MTI-II) from the livers of adrenalectomized rats to apparent homogeneity as judged by two-dimensional PAGE. Purified MTI-II inhibits GR binding to DNA containing glucocorticoid-response elements. To obtain the amino acid sequence of MTI-II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 40 publications
(50 reference statements)
0
13
0
1
Order By: Relevance
“…Early studies have identified ParaT as a zinc-binding protein, which interacts with several enzymes involved in carbohydrate metabolism (30,31). Recently, ParaT was found to inhibit the binding of the activated glucocorticoid receptor to nuclei, suggesting its involvement in the regulation of glucocorticoid steroids action (32).…”
mentioning
confidence: 99%
“…Early studies have identified ParaT as a zinc-binding protein, which interacts with several enzymes involved in carbohydrate metabolism (30,31). Recently, ParaT was found to inhibit the binding of the activated glucocorticoid receptor to nuclei, suggesting its involvement in the regulation of glucocorticoid steroids action (32).…”
mentioning
confidence: 99%
“…In previous in vitro experiments (8), we found that highly purified GR binds to an MTI-II affinity matrix. In the context of the findings on PT␣, we speculated that MTI-II might be involved in regulating the transcriptional activity of GR in vivo.…”
mentioning
confidence: 75%
“…Hormone-We previously showed that highly purified GR binds to an MTI-II affinity matrix in vitro and is eluted from the matrix with 200 mM NaCl (8). To elucidate whether MTI-II interacts with GR in vivo, we examined whether MTI-II could be co-immunoprecipitated with the intrinsic GR and vice versa.…”
Section: Mti-ii Interacts With Gr In Vivo In the Presence Of Glucocormentioning
confidence: 99%
See 1 more Smart Citation
“…PTMA and PTMS, which were originally obtained by bovine thymus extraction, are members of the α-thymosin family (24). Previous studies have demonstrated that PTMA and PTMS activate the immune response to curb the viral infection in patients with human immunodeficiency virus, hepatitis B virus or hepatitis C virus (25,26).…”
Section: Discussionmentioning
confidence: 99%